34.1k views
5 votes
Does anyone mind helping me with this? It seems simple enough.

The question is: Radical x-3 = radical x + 3 (the +3 is outside of the radical). We are solving for X in this question.

1 Answer

4 votes

Answer:

x = 4

Explanation:

It is given that
√((x - 3)) = √(x) + 3, and we have to solve the given equation for x.

Now, we have
√((x - 3)) = √(x) + 3

Squaring both sides we get


[√((x - 3))] ^(2) = [√(x) + 3]^(2)

⇒ x - 3 = x + 6√x + 9 {Since we know the formula of (a + b)² = a² + 2ab + b²}

⇒ 6√x = - 12

√x = -2

Again squaring both sides we get

⇒x = 4 (Answer)

User David Dale
by
6.3k points